Neuromorphic hybrid systems based on polarizable thin film-coated silicon nanowire field-effect transistors - Panes-Ruiz, Luis Antonio; Ibarlucea, Bergoi; Baek, Eunhye; Park, Sang Wook; Baek, Chang Ki; Feng, Xinliang; Cuniberti, Gianaurelio (Giovanni) (International Workshop on Cellular Nanoscale Networks and their Applications, 2021)
We present two approaches for the development of hybrid neurotransistors based on the combination of polarizable thin films on silicon nanowires field-effect transistors for the emulation of signal processing by neurons. The polarizing properties of the films coming from the ion redistribution under bias voltage provide the systems with a memristive behavior needed to achieve the neuronal intrinsic plasticity using ionic migration in the neuron membrane at a hardware level.
CRIS-Team Scopus Importer:2023-03-20
Keywords: BECOFs; neuromorphic architecture; silicon nanowire field-effect transistor; sol-gel; thin films